Analysis of Junior High School Students’ Mathematical Representation Ability Based on Self-Efficacy in Relations and Functions - Sagita, Yan Ayu Lintang; Fendiyanto, Petrus (Jurnal Paedagogy, 2026)
This study aims to analyze students’ mathematical representation abilities in relation to their levels of self-efficacy in learning the topic of relations and functions. Employing a descriptive qualitative approach, this study involved 23 eighth-grade students from a public junior high school in East Kalimantan, Indonesia. Based on the results of a self-efficacy questionnaire, students were classified into three groups: high, moderate, and low self-efficacy. Six students were then purposively selected for further in-depth analysis using a mathematical representation ability test and semi-structured interviews. Data were analyzed through the processes of data condensation, data display, and conclusion drawing, with source triangulation applied to ensure the credibility of the findings. The results showed that students with high self-efficacy demonstrated a very high level of mathematical representation ability (87.5%) and consistently employed visual, symbolic, and verbal representations. Students with moderate self-efficacy achieved a moderate level of mathematical representation ability (58.33%), indicating sufficient conceptual understanding but inconsistencies in procedural application. Meanwhile, students with low self-efficacy exhibited a low level of mathematical representation ability (20.83%), characterized by limited confidence and difficulties in expressing mathematical ideas effectively. These findings suggest that teachers should design learning experiences that simultaneously enhance students’ self-efficacy and encourage the use of various mathematical representations, including visual, symbolic, and verbal forms. Furthermore, curriculum developers should develop instructional activities and assessment frameworks that integrate multiple representation modes while fostering students’ confidence in communicating mathematical ideas. Such efforts may contribute to deeper mathematical understanding and improved problem-solving skills.